Positive electrode material, positive plate and battery
By preparing the positive electrode material of Lixniacobncmdo2, the number of cracks and crystal cell parameters of the particle surface cracks is controlled to solve the problem of poor production and stability in the cycle in the cycle, and achieve the effect of high magnification performance and long cycle life.
Patent Information
- Application Number
- CN202411931254.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
AI Technical Summary
The existing positive electrode materials have obvious gas production effects during the charge and discharge cycle, poor circulation stability, and it is difficult to balance the rate performance and circulation stability.
By preparing the positive electrode material of Lixniacobncmdo2, the proportion of the number of cracks on the surface of the particles is controlled ≤13%, and the volume of crystal cells and C/A is controlled to make it less than 104.2å3 and greater than 4.82.
Effectively reduce the crystal structure defects, improve the phenomenon of gas production, improve the cycle stability and magnification performance of the positive pole material, and achieve a comprehensive improvement of structural stability and electrochemical properties.
Smart Images

Figure CN119361682A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to positive electrode materials, positive electrode sheets and batteries. Background Art
[0002] Lithium-ion batteries (LIBs) have the advantages of high energy density, high power density, long cycle life and low self-discharge, so they are widely used in 3C electronic products, electric vehicles and energy storage. As the core component of lithium-ion batteries, the positive electrode material directly determines the operating voltage and storage capacity of the battery. Among the many positive electrode materials, ternary positive electrode materials have become the most widely used positive electrode materials in the field of lithium-ion batteries due to their advantages of high specific capacity and high voltage platform. However, the current positive electrode materials have obvious gas production effect during the charge and discharge cycle and poor cycle stability.
[0003] Although surface coating treatment can generally be used to maintain the interface stability of the positive electrode material and improve the gas generation defects of the positive electrode material, such improvement measures cannot fundamentally solve the related defects of the positive electrode material and it is difficult to balance the rate performance and cycle stability of the positive electrode material. Summary of the invention
[0004] The present application provides a positive electrode material, a positive electrode sheet, and a battery. The positive electrode material of the present application can reduce crystal structure defects, improve the gas production phenomenon of the positive electrode material, and achieve a balance between high-rate performance and cycle stability.
[0005] In a first aspect, the present application provides a positive electrode material, the chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.5≤a<0.6, 0.08≤b≤0.14, 0.30≤c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, and M is a metal element; the positive electrode material includes a plurality of particles; A cross-sectional SEM image of the positive electrode material is measured at a magnification of 3K by a scanning electron microscope, and 200 particles in the cross-sectional SEM image are randomly measured, and the number of particles with cracks in the cross-sectional SEM image accounts for ≤13%; The positive electrode material is subjected to XRD measurement using Cu-Kα rays, and the unit cell volume V of the positive electrode material is less than 104.2Å. 3 The relationship between the unit cell parameter c of the c-axis and the unit cell parameter a of the a-axis of the positive electrode material satisfies: c / a>4.82.
[0006] In some embodiments, a ≤ 2.901 Å.
[0007] In some embodiments, c≤14.2520 Å.
[0008] In some embodiments, the unit cell parameter Dp of the positive electrode material is 90 nm-120 nm.
[0009] In some embodiments, the lattice strain of the cathode material is less than 0.3%.
[0010] In some embodiments, the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn, and Y.
[0011] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 0.9≤(D 90 -D 10 ) / D 50 ≤1.6.
[0012] In some embodiments, the particles have a single crystalline structure.
[0013] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.0m 2 / g.
[0014] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 1.9<ρ1<2.7.
[0015] In some embodiments, the compaction density of the positive electrode material is p2 g / cm 3 , 3.0≤ρ2<3.5.
[0016] In some embodiments, the gas generation value of the positive electrode material is 0.1 mL / g to 1 mL / g.
[0017] In some embodiments, a SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the wide diameter that perpendicularly bisects the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.6.
[0018] In a second aspect, the present application provides a positive electrode sheet, comprising the positive electrode material as described above, wherein in the positive electrode sheet, the number of particles of the positive electrode material having cracks accounts for 1.5% to 13% of the total number of particles of the positive electrode material.
[0019] In a third aspect, the present application provides a battery, comprising the positive electrode material described in the first aspect.
[0020] Compared with the prior art, the technical solution of the present application has at least the following beneficial effects: The positive electrode material provided in the present application is prone to cracks on the surface of the particles of the positive electrode material due to high-temperature sintering during the preparation process. These cracks are prone to lattice deformation during the charge and discharge cycle due to the particles' deintercalation of lithium ions. The presence of cracks makes the positive electrode material particles more likely to break, resulting in aggravated side reactions between the positive electrode material and the electrolyte, and reduced cycle stability of the positive electrode material. Therefore, the present application controls the number of particles with cracks in the positive electrode material to account for ≤13%, so that the number of particles with cracks is controlled within an appropriate range, which can reduce particle breakage caused by expansion stress and improve the structural stability and cycle stability of the positive electrode material particles; at the same time, the unit cell volume V of the positive electrode material is controlled to be less than 104.2Å 3 , a smaller unit cell volume is conducive to maintaining the stability of the crystal structure, reducing the volume change during the charge and discharge process, and improving the compressive strength and electronic conductivity of the particles. However, too small a unit cell volume and structural defects will increase the internal resistance of lithium ion transmission during the charge and discharge process, which is not conducive to improving the rate performance of the positive electrode material. Therefore, while controlling the unit cell volume V of the positive electrode material, the unit cell parameter c / a ratio of the positive electrode material is increased, so that c / a>4.82. As the c / a ratio increases, the layered structure has fewer defects, which is conducive to the transmission of lithium ions and increases the rate, thereby compensating for the negative impact of the reduction in unit cell volume. In this application, by making the unit cell volume of the positive electrode material and the number of particles with cracks within the above range, the crystal structure stability of the positive electrode material can be effectively improved, the particle breakage can be reduced, and the cycle stability of the positive electrode material can be improved. Then, the unit cell parameter c / a of the positive electrode material is adjusted to improve the rate performance of the positive electrode material, thereby achieving a comprehensive improvement in the cycle stability and gas production of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0022] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.
[0023] Figure 2 This is a SEM image of the cross-section of the positive electrode sheet prepared in Example 1 of the present application.
[0024] Figure 3 This is a cross-sectional SEM image of the positive electrode sheet prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0025] In order to better understand the technical solution of the present invention, the embodiments of the present invention are described in detail below with reference to the accompanying drawings.
[0026] It should be clear that the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0028] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0029] The high-temperature sintering process of the positive electrode material will lead to the formation of surface cracks. The cracks will expose more active sites inside the particles to react with the electrolyte, accelerate the capacity decay of the positive electrode material, reduce the structural stability and cycle stability of the positive electrode material, and thus reduce the cycle performance of the battery.
[0030] In summary, cracks are the main reason for the decline in the cycle performance of positive electrode materials. Cracks will destroy the structure of positive electrode materials and reduce the structural stability and cycle stability of positive electrode materials. Once cracks are formed on the surface of particles, the electrolyte will enter the interior of the positive electrode material particles along the cracks, react with the transition metal, cause the transition metal to dissolve, seriously damage the particle structure of the positive electrode material, and eventually cause the particles to break, reducing the overall structural stability and cycle performance of the positive electrode material.
[0031] In the first aspect, the present application provides a positive electrode material, the chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.5≤a<0.6, 0.08≤b≤0.14, 0.30≤c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, M is a metal element; A cross-sectional SEM image of the positive electrode material is measured at a magnification of 3K by a scanning electron microscope, and 200 particles in the cross-sectional SEM image are randomly measured, and the number of particles with cracks in the cross-sectional SEM image accounts for ≤13%; The positive electrode material is subjected to XRD measurement using Cu-Kα rays, and the unit cell volume V of the positive electrode material is less than 104.2Å. 3 The relationship between the unit cell parameter c of the c-axis and the unit cell parameter a of the a-axis of the positive electrode material satisfies: c / a>4.82.
[0032] The positive electrode material provided in the present application is prone to cracks on the surface of the particles of the positive electrode material due to high-temperature sintering during the preparation process. These cracks are prone to lattice deformation during the charge and discharge cycle due to the particles' deintercalation of lithium ions. The presence of cracks makes the positive electrode material particles more likely to break, resulting in aggravated side reactions between the positive electrode material and the electrolyte, and reduced cycle stability of the positive electrode material. Therefore, the present application controls the number of particles with cracks in the positive electrode material to account for ≤13%, so that the number of particles with cracks is controlled within an appropriate range, which can reduce particle breakage caused by expansion stress and improve the structural stability and cycle stability of the positive electrode material particles; at the same time, the unit cell volume V of the positive electrode material is controlled to be less than 104.2Å 3 , a smaller unit cell volume is conducive to maintaining the stability of the crystal structure, reducing the volume change during the charge and discharge process, and improving the compressive strength and electronic conductivity of the particles. However, too small a unit cell volume and structural defects will increase the internal resistance of lithium ion transmission during the charge and discharge process, which is not conducive to improving the rate performance of the positive electrode material. Therefore, while controlling the unit cell volume V of the positive electrode material, the unit cell parameter c / a ratio of the positive electrode material is increased, so that c / a>4.82. As the c / a ratio increases, the layered structure has fewer defects, which is conducive to the transmission of lithium ions and increases the rate, thereby compensating for the negative impact of the reduction in unit cell volume. In this application, by the unit cell volume of the positive electrode material and the number of particles with cracks being within the above range, the two can synergistically improve the crystal structure stability of the positive electrode material, reduce particle breakage, and improve the cycle stability of the positive electrode material. Then, the unit cell parameter c / a of the positive electrode material is adjusted to improve the rate performance of the positive electrode material, thereby achieving a comprehensive improvement in the cycle stability and gas production of the positive electrode material.
[0033] In some embodiments, the positive electrode material has the general chemical formula Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.5≤a<0.6, 0.08≤b≤0.14, 0.30≤c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, and M is a metal element.
[0034] The specific value of x can be 0.98, 0.99, 1.0, 1.02, 1.04, 1.05, 1.07, 1.08, 1.09 or 1.1, the specific value of a can be 0.5, 0.51, 0.52, 0.53, 0.54, 0.55, 0.56, 0.57, 0.58 or 0.59, and the specific value of b can be 0.08, 0.09, 0. 1, 0.11, 0.12, 0.13 or 0.14, etc., the value of c can be 0.30, 031, 0.32, 0.33, 0.34 or 0.35, etc., the value of d can be 0, 0.001, 0.005, 0.006, 0.008, 0.009, 0.01, 0.02, 0.03, 0.05, 0.07 or 0.1, etc., and is not limited here.
[0035] In some embodiments, the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y. It can be understood that an appropriate amount of M element doping can improve the lattice structure stability of the positive electrode material and reduce lithium-nickel mixing.
[0036] In some embodiments, the number of particles with cracks in the cross-section SEM image is ≤13%, specifically 13%, 11%, 10%, 8%, 6%, 5%, 4%, 3%, 2%, 1.5%, 1.0%, 0.5%, etc., and of course other values within the above range, which are not limited here. When the number of particles with cracks accounts for too much, the cracks will expose more active sites inside the particles to react with the electrolyte, accelerate the capacity decay of the positive electrode material, increase gas production, reduce the structural stability and cycle stability of the positive electrode material, and thus reduce the cycle performance of the battery.
[0037] In some embodiments, the cathode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume V of the cathode material is less than 104.2 Å. 3 , V can be specifically 100.80Å 3 , 100.90Å 3 , 101.2Å 3 , 101.4Å 3 , 101.5Å 3 , 101.8Å 3 , 102.5Å 3 , 103.4Å 3 , 103.8Å 3 , 104.1 Å 3 Of course, it can also be other values within the above range and is not limited here.
[0038] In the present application, the unit cell volume of the positive electrode material is within the above range, the distance between transition metal atoms is shorter, and the bond energy between transition metal atoms is stronger, so that the expansion of cracks on the particle surface and extension to the interior of the particle requires overcoming a higher potential barrier, thereby inhibiting the diffusion of cracks and improving cycle stability. However, during the process of lithium ion insertion or extraction, the lattice will expand or contract, causing stress inside the unit cell, and a smaller unit cell volume also means that it will cause greater local stress concentration, thereby promoting the diffusion of cracks during the charge and discharge process. Therefore, the present application controls V < 104.2Å 3 , so that the unit cell volume is within an appropriate range, which is beneficial to maintaining the stability of the crystal structure, reducing the volume change during charging and discharging, and improving the compressive strength and electronic conductivity of the particles.
[0039] In some embodiments, the positive electrode material is subjected to XRD measurement using Cu-Kα rays, and the positive electrode material unit cell parameter ratio is c / a, c / a>4.82. c / a can be 4.821, 4.825, 4.83, 4.84, 4.85, 4.86, 4.89, 4.90, etc., which are not limited here.
[0040] In some embodiments, the unit cell parameter a of the a-axis of the positive electrode material is ≤2.901 Å, and may specifically be 2.901Å, 2.900Å, 2.898Å, 2.897Å, 2.895Å, 2.893Å, etc., and may of course be other values within the above range, which is not limited here.
[0041] In some embodiments, the unit cell parameter c of the c-axis of the positive electrode material is ≤14.2520Å, and may be specifically 14.2520Å, 14.2500Å, 14.2490Å, 14.2480Å, 14.2460Å, 14.2220Å, etc., and may be other values within the above range, which is not limited here.
[0042] In some embodiments, the positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell parameter Dp of the positive electrode material is Dp=D 003 +D 104 , Dp is 90nm~120nm, specifically 90nm, 95nm, 100nm, 105nm, 110nm, 115nm or 120nm, etc., but it is not limited to the listed values, and other values not listed in this range are also applicable. By measuring the diffraction angles corresponding to the (003) and (104) crystal plane diffraction peaks in the XRD spectrum, D can be calculated. 003 , D 104 The average value of the two is Dp.
[0043] In the present application, the unit cell parameter Dp and unit cell parameter ratio c / a of the positive electrode material are within the above range, which indicates that the crystal structure of the positive electrode material is stable, the internal doping of the positive electrode material is uniform, and the internal defects of the positive electrode material crystal can be reduced, which is beneficial to the improvement of the capacity of the positive electrode material.
[0044] In some embodiments, the median particle size D50 of the positive electrode material is 2.0 μm to 6.0 μm, specifically 2.0 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, 5.5 μm or 6.0 μm, etc., and of course, other values within the above range are also possible, which are not limited here. Since the median particle size of the positive electrode material is within the above range, the particles within this size range have better electrochemical properties, higher discharge capacity and excellent rate performance.
[0045] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 0.9≤(D 90 -D 10 ) / D 50 ≤1.6, specifically 1.05, 1.08, 1.1, 1.15, 1.18, 1.2, 1.22, 1.25, 1.26, 1.3, 1.35, 1.4, 1.5 or 1.6, etc., and of course other values within the above range are also possible, which are not limited here. In the present application, by controlling the particle size distribution width of the positive electrode material within the above range, particles of different sizes can be stacked more closely, so that the compaction density of the positive electrode sheet is improved and the energy density is higher.
[0046] In some embodiments, the positive electrode material is a single crystal material, and the positive electrode material includes single crystal particles, and the single crystal particles are particles with the same orientation. It should be specially noted that the "single crystal material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in reality. Therefore, the single crystal material known in the art is actually more of a "single crystal morphology" positive electrode material, which only shows a single crystal-like large particle size in size, which is different from the polycrystalline particles composed of many small particles.
[0047] The single crystal grain in the present application may be a single particle composed of one primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several primary particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope.
[0048] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nano-scale particles. For single crystal positive electrode materials, the smallest particle is usually a single particle of micrometer size. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and orientation. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0049] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.0m 2 / g. Specifically, it can be 0.5m 2 / g, 0.55 m 2 / g, 0.6 m 2 / g, 0.65 m 2 / g, 0.7 m 2 / g, 0.75 m 2 / g, 0.8 m 2 / g, 0.85 m 2 / g, 0.9 m 2 / g, 0.95 m 2 / g or 1.0 m 2 / g, etc., and of course, other values within the above range may also be possible, which are not limited here. The specific surface area of the positive electrode material can be controlled within the above range, which can effectively reduce the side reaction between the positive electrode material and the electrolyte and improve the capacity of the positive electrode material.
[0050] In some embodiments, the tap density of the positive electrode material is ρ1 g / cm 3 , 1.9<ρ1<2.7, specifically 1.91g / cm 3 , 1.95g / cm 3 , 2.0g / cm 3, 2.1g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 or 2.69 g / cm 3 Of course, it can also be other values within the above range, which is not limited here.
[0051] In some embodiments, the compacted density of the positive electrode material is p2 g / cm 3 , 3.0≤ρ2<3.5, specifically 3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.25g / cm 3 , 3.3g / cm 3 、3.35g / cm 3 、3.4g / cm 3 、3.45g / cm 3 or 3.49 g / cm 3 Of course, it can also be other values within the above range, which is not limited here.
[0052] In some embodiments, the gas production value of the positive electrode material is 0.1mL / g~1mL / g, specifically 0.1mL / g, 0.2mL / g, 0.3mL / g, 0.4mL / g, 0.5mL / g, 0.6mL / g, 0.7mL / g, 0.8mL / g or 1mL / g, etc. Of course, it can also be other values within the above range, which is not limited here.
[0053] In some embodiments, the SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, and the average size of the wide diameter that vertically divides the longest diameter of the particle is L. The average aspect ratio of the particles is α=D / L, 1≤α≤1.6, which can be 1, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55 or 1.6, etc., and of course, it can also be other values within the above range, which is not limited here. When the average aspect ratio of the particles is within the above range, the particles have a high degree of roundness and no obvious edges and corners, which is beneficial to reducing the specific surface area of the positive electrode material, reducing the direct contact between the positive electrode material and the electrolyte, and reducing the occurrence of side reactions; and the aspect ratio is controlled within the above range, which is beneficial to the uniform dispersion of the particle expansion stress and the reduction of local stress accumulation. The present application synergistically controls the average aspect ratio of the particles and the number of particles with cracks, which can further reduce the occurrence of side reactions between the electrolyte and the positive electrode material and improve the structural stability and cycle stability of the positive electrode material.
[0054] In a second aspect, the present application provides a method for preparing the above-mentioned positive electrode material, comprising the following steps: Step S10, prepare a salt solution of nickel, manganese and N elements, prepare a mixed solution according to a certain stoichiometric ratio, add an appropriate amount of complexing agent, so that the concentration of the complexing agent in the mixed solution is 0.5 mol / L~2 mol / L, and adopt a spray pyrolysis process to prepare a positive electrode material precursor, control the pyrolysis temperature T and the size of the atomized droplet diameter d D50 to satisfy T=(2000+600d) / (d+2), and the N element is Mn or Al.
[0055] In some embodiments, the stoichiometric ratio of nickel, cobalt, and N elements meets the following conditions: 0.5≤Ni≤0.6, 0.08≤Co≤0.15, and 0.30≤Mn≤0.35.
[0056] In some embodiments, the salt solution is at least one of nitrate, hydrochloride, sulfate, carbonate, oxalate, and acetate. For example, the nickel salt solution can be at least one of nickel chloride, nickel sulfate, nickel nitrate, nickel carbonate, nickel oxalate, and nickel acetate. Of course, nickel, manganese, and cobalt can also be metal elemental raw materials or recycled materials of ternary positive electrode materials, which are not limited here.
[0057] In some embodiments, the complexing agent includes at least one of phosphates, alcohol amines, aminocarboxylates, hydroxycarboxylates, organic phosphonates, and polyacrylic acids.
[0058] In some embodiments, the complexing agent is phosphate, and the size of the atomized droplets is controlled to be between 1 μm and 15 μm.
[0059] In some embodiments, the complexing agent is an aminocarboxylate, and the size of the atomized droplets is controlled to be 4 μm to 18 μm.
[0060] In some embodiments, the complexing agent is an alcohol amine, and the size of the atomized droplets is controlled to be 4 μm to 17 μm.
[0061] In some embodiments, the complexing agent is a hydroxycarboxylate, and the size of the atomized droplets is controlled to be between 8 μm and 16 μm.
[0062] In some embodiments, the complexing agent is an organic phosphonate, and the size of the atomized droplets is controlled to be 5 μm to 12 μm.
[0063] In some embodiments, the complexing agent is polyacrylic acid, and the size of the atomized droplets is controlled to be 8 μm to 20 μm.
[0064] In some embodiments, the complexing agent is added to the mixed solution twice, and the time interval between the two additions is 1 hour to 6 hours.
[0065] In some embodiments, the concentration of the complexing agent in the mixed solution is 0.2 mol / L~3 mol / L, specifically 0.2 mol / L, 0.4 mol / L, 0.5 mol / L, 0.8 mol / L, 0.9 mol / L, 1.0 mol / L, 1.2 mol / L, 1.3 mol / L, 1.5 mol / L, 1.8 mol / L, 2.0 mol / L, 2.2 mol / L, 2.5 mol / L, 2.8 mol / L or 3.0 mol / L, etc., and of course it can also be other values within the above range, which is not limited here.
[0066] It should be noted that the addition of different types of chelating agents can form complexes with metal ions in the salt solution, thereby optimizing the crystal structure of the cathode material precursor, making the layered structure of the cathode material precursor more stable, and improving the diffusion efficiency of lithium ions.
[0067] In some embodiments, the pyrolysis temperature T and the atomized droplet diameter d are controlled to satisfy D50 T=(2000+600d) / (d+2). The atomized droplet diameter can be obtained by laser particle size analyzer testing.
[0068] In some embodiments, the atomization flow rate of the mixed solution during spray pyrolysis is 5 L / min~20 L / min, specifically 5 L / min, 8 L / min, 10 L / min, 12 L / min, 15 L / min, 18 L / min or 20 L / min, etc., and of course it can also be other values within the above range, which are not limited here.
[0069] In some embodiments, a compound containing element M is further added to the mixed solution according to a target doping ratio, which may specifically be a nitrate containing element M, a hydrochloride containing element M, an acid containing element M, etc., which is not limited here.
[0070] In some embodiments, the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn, and Y.
[0071] Step S20, mixing the positive electrode material precursor, the lithium source, and the doping flux to obtain a first mixture, and performing a primary sintering treatment on the first mixture to obtain a primary sintering product.
[0072] In some embodiments, the lithium source includes at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate, and lithium oxalate.
[0073] In some embodiments, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal in the nickel-cobalt-manganese-based oxide precursor is controlled to be 1.0≤n Li / n Me ≤1.1; specifically, it can be 1.0:1, 1.01:1, 1.02:1, 1.03:1, 1.04:1, 1.05:1, 1.06:1, 1.07:1, 1.08:1, 1.09:1 or 1.1:1, etc. Of course, it can also be other values within the above range, which is not limited here.
[0074] In some embodiments, the dopant includes a compound containing an M element, and the M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
[0075] In some embodiments, based on the mass of the positive electrode material precursor as 100%, the added amount of the doping flux is 0.001%~0.4%, specifically 0.001%, 0.002%, 0.06%, 0.10%, 0.15%, 0.22%, 0.32%, 0.36% or 0.4%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In some embodiments, the doping flux includes a transition metal oxide with a low melting point, specifically tungsten oxide, strontium oxide, titanium oxide, and yttrium oxide. It can be understood that the transition oxide helps the growth of single crystal particles and repairs cracks formed during the growth process. The doping flux will accelerate the growth of single crystals in the early stage of the primary sintering process, and help repair intercrystalline cracks of particles in the later stage of the primary sintering process, and help the primary sintering product become rounded and dispersed single crystal particles.
[0077] In some embodiments, the mixing is performed in a mixing device, which may be a high-speed mixer, a ball mill mixer, a VC mixer, or a three-dimensional mixer, etc. The device may be selected according to actual needs and is not limited here.
[0078] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, and the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.
[0079] In some embodiments, the temperature of a sintering treatment is 800°C~1000°C, specifically 800°C, 820°C, 830°C, 850°C, 870°C, 900°C, 950°C, 980°C, 990°C or 1000°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0080] In some embodiments, the time for a sintering treatment is 6 h to 12 h, specifically 6 h, 6.5 h, 7 h, 8 h, 9 h, 10 h, 11 h or 12 h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0081] Step S30, air flow pulverizing the primary sintered product, mixing the air flow pulverized product with a coating agent, and then performing a secondary sintering treatment to obtain a positive electrode material.
[0082] In some embodiments, during the air flow crushing process, the weight of the grinding body is controlled to be 20% to 60% of the design upper limit of the equipment grinding body weight, that is, 200-1200g, specifically 200g, 300g, 400g, 800g, 1000g, 1100g or 1200g, etc., and of course, it can also be other values within the above range, which is not limited here.
[0083] In some embodiments, during the air flow pulverizing process, the pulverizing air pressure is controlled at 0.4 Mpa~0.65 Mpa, specifically 0.4 Mpa, 0.5 Mpa, 0.55 Mpa, 0.6 Mpa or 0.65 Mpa, etc. Of course, it can also be other values within the above range, which is not limited here.
[0084] In some embodiments, the average aspect ratio of particles in the airflow milling product is 1 to 1.6, specifically 1, 1.1, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.55 or 1.6, etc., and of course it can also be other values within the above range, which is not limited here.
[0085] In some embodiments, based on the mass of the pulverized product as 100%, the amount of the coating agent added is 0.05% to 0.4%, specifically 0.05%, 0.06%, 0.07%, 0.08%, 0.1%, 0.12%, 0.15%, 0.2%, 0.25%, 0.28%, 0.3%, 0.35% or 0.4%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] In some embodiments, the coating agent includes a compound containing the N element, and the N element includes at least one of Ti, Zr, Al, Y, W, and Co.
[0087] In some embodiments, the coating process is carried out under stirring, and the stirring speed is controlled to be 100 rpm to 700 rpm, specifically 100 rpm, 150 rpm, 250 rpm, 350 rpm, 400 rpm, 550 rpm, 650 rpm or 700 rpm, etc., and of course, other values within the above range can also be used, which are not limited here. Preferably, the stirring speed is 450 rpm.
[0088] In some embodiments, the oxygen concentration in the oxygen-containing atmosphere is ≥ 95%.
[0089] In some embodiments, the temperature of the secondary sintering treatment is 350°C~600°C, specifically 350°C, 360°C, 380°C, 400°C, 420°C, 480°C, 500°C, 550°C or 600°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0090] In some embodiments, the time of the secondary sintering treatment is 5h~10h, specifically 5h, 5.5h, 6h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h or 10h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0091] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.
[0092] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag obtained by packaging with a packaging film (such as an aluminum-plastic film), such as a soft-pack battery.
[0093] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.
[0094] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.
[0095] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0096] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .
[0097] In some embodiments, in the positive electrode sheet, the number of particles of the positive electrode material with cracks accounts for 1.5% to 13% of the total number of particles of the positive electrode material, and can be specifically 13%, 11%, 10%, 8%, 6%, 5%, 4%, 3%, 2%, 1.5%, etc., and of course, it can also be other values within the above range, which are not limited here. When the number of particles of the positive electrode material with cracks accounts for too much, the cracks will expose more active sites inside the particles to react with the electrolyte, accelerate the capacity decay of the positive electrode sheet, intensify gas production, and reduce the battery cycle stability.
[0098] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.
[0099] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.
[0100] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0101] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0102] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0103] Example 1 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonic for 2 h. Add ammonium phosphate as a complexing agent in two additions. The total addition time is 3 h. The interval between the two additions is 1 h. The first addition time is 1 h, and the second addition time is 1 h. The final concentration of ammonium phosphate in the mixed solution is 0.5 mol / L. Spray granulate the mixed solution. The atomization flow rate is controlled to be 10 L / min. The size of the atomized droplet D50 is 8 μm. The pyrolysis temperature is 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0104] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.2g Al2O3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0105] (3) The primary sintered product was subjected to air flow milling, the grinding mass was controlled at 400 g, the air pressure was controlled at 0.65 MPa, and the specific surface area of the air flow milling product was 0.6 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.2.
[0106] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0107] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is Al and the coating element is Ti. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0108] Example 2 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 3 h. Add ammonium phosphate as a complexing agent in two additions, the addition time is 4 h, the interval between the two additions is 2 h, the first addition time is 1 h, and the second addition time is 1 h. The final concentration of ammonium phosphate in the mixed solution is 0.6 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the D50 size of the atomized droplets to 6 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0109] (2) 200gNi precursor 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 94.8g Li2CO3, and 0.4g W2O3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 970°C for a primary sintering treatment to obtain a primary sintering product.
[0110] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 600 g, the air pressure was controlled at 0.45 MPa, and the specific surface area of the air flow milling product was 0.7 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.4.
[0111] (4) 100 g of the air flow pulverized product was mixed with 0.2 g of ZrO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0112] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30O2, where the doping element is W and the coating element is Zr. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0113] Example 3 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add ammonium carbamate as a complexing agent in two additions, the addition time is 3 h, the interval between the two additions is 0.5 h, the first addition time is 1.5 h, and the second addition time is 0.5 h. The final concentration of ammonium carbamate in the mixed solution is 0.8 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 12 L / min, the size of the atomized droplet D50 to 10 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0114] (2) 500gNi precursor 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 220g Li2CO3, and 2.4g WO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0115] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 400 g and the air pressure was controlled at 0.40 MPa. The specific surface area of the air flow milling product was 0.6 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.3.
[0116] (4) 200 g of the air flow pulverized product was mixed with 0.3 g of ZrO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0117] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, where the doping element is W and the coating element is Zr. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0118] Example 4 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 2 h, add alcohol amine as a complexing agent, add it twice, the addition time is 3 h, the interval between the two times is 0.5 h, the first continuous addition time is 1.5 h, and the second continuous addition time is 0.5 h. The final concentration of alcohol amine in the mixed solution is 1 mol / L. The mixed solution is sprayed and granulated, the atomization flow rate is controlled to be 10 L / min, the size D50 of the atomized droplets is 12 μm, and the pyrolysis temperature is 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0119] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 210g Li2CO3, and 1.9g SrO are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 970°C for a primary sintering treatment to obtain a primary sintering product.
[0120] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 1200 g and the air pressure was controlled at 0.5 MPa. The specific surface area of the air flow milling product was 0.7 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.6.
[0121] (4) 200 g of the air flow pulverized product was mixed with 0.3 g of ZrO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0122] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is Sr and the coating element is Zr. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0123] Example 5 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 58:12:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add ammonium phosphonate as a complexing agent in two additions, the addition time is 3 h, the interval between the two additions is 2 h, the first addition time is 0.5 h, and the second addition time is 0.5 h. The final concentration of ammonium phosphonate in the mixed solution is 2 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 15 L / min, the size of the atomized droplet D50 to 8 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.58 Co 0.12 Mn 0.3 O x (0.8<x<1.2).
[0124] (2) 500g Ni 0.58 Co 0.12 Mn 0.3 O x (0.8<x<1.2), 240g LiOH·H2O, and 2.5g SrCO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 960°C for a primary sintering treatment to obtain a primary sintering product.
[0125] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 800 g and the air pressure was controlled at 0.5 MPa. The specific surface area of the air flow milling product was 0.7 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.5.
[0126] (4) 200 g of the air flow pulverized product was mixed with 0.6 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0127] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.58 Co 0.12 Mn 0.30 O2, in which the doping element is Sr and the coating element is Al. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0128] Example 6 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 58:12:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add aminocarboxylate as a complexing agent in two additions, with an addition time of 2 h and an interval of 0.5 h between the two additions. The first addition time is 0.5 h and the second addition time is 1 h. The final concentration of aminocarboxylate in the mixed solution is 2 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 15 L / min, the size of the atomized droplet D50 to 15 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.58 Co 0.12 Mn 0.3 O x (0.8<x<1.2).
[0129] (2) 500g Ni 0.58 Co 0.12 Mn 0.3 O x (0.8<x<1.2), 240g LiOH·H2O, and 2.5g WO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 960° C. for a primary sintering treatment to obtain a primary sintering product.
[0130] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 1200 g and the air pressure was controlled at 0.4 MPa. The specific surface area of the air flow milling product was 0.65 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.6.
[0131] (4) 200 g of the air flow pulverized product was mixed with 0.6 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0132] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.58 Co 0.12 Mn 0.30 O2, where the doping element is W and the coating element is Al. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0133] Example 7 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add ammonium phosphate as a complexing agent in two additions, the addition time is 2 h, the interval between the two additions is 1 h, the first addition time is 0.5 h, and the second addition time is 0.5 h. The final concentration of ammonium phosphate in the mixed solution is 2 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 15 L / min, the size of the atomized droplet D50 to 8 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0134] (2) 500gNi precursor 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 240g LiOH·H2O, and 2.5g SrCO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 965°C for a primary sintering treatment to obtain a primary sintering product.
[0135] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 400 g and the air pressure was controlled at 0.5 MPa. The specific surface area of the air flow milling product was 0.6 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.25.
[0136] (4) 200 g of the air flow pulverized product was mixed with 0.6 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0137] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is Sr and the coating element is Al. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0138] Example 8 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add aminocarboxylate as a complexing agent in two additions, with an addition time of 2 h and an interval of 0.5 h between the two additions. The first addition time is 1 h and the second addition time is 0.5 h. The final concentration of aminocarboxylate in the mixed solution is 2 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 15 L / min, the size of the atomized droplet D50 to 15 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0139] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 240g LiOH·H2O, and 2.5g WO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 960° C. for a primary sintering treatment to obtain a primary sintering product.
[0140] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 800 g and the air pressure was controlled at 0.5 MPa. The specific surface area of the air flow milling product was 0.65 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.35.
[0141] (4) 200 g of the air flow pulverized product was mixed with 0.6 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0142] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, where the doping element is W and the coating element is Al. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0143] Example 9 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2 h. Add ammonium phosphonate as a complexing agent in two additions, with an addition time of 2.5 h and an interval of 0.5 h between the two additions. The first addition time is 1 h and the second addition time is 1 h. The final concentration of ammonium phosphonate in the mixed solution is 0.5 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplet D50 to 8 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0144] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.2g Al2O3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0145] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 200 g and the air pressure was controlled at 0.4 MPa. The specific surface area of the air flow milling product was 0.6 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.18.
[0146] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0147] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is Al and the coating element is Ti. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0148] Example 10 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2 h. Add ammonium phosphonate as a complexing agent in two additions, the addition time is 1.5 h, the interval between the two additions is 0.5 h, the first addition time is 0.5 h, and the second addition time is 0.5 h. The final concentration of ammonium phosphonate in the mixed solution is 0.5 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the size of the atomized droplet D50 to 8 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0149] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.2g Al2O3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0150] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 1200 g and the air pressure was controlled at 0.65 MPa. The specific surface area of the air flow milling product was 0.9 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.6.
[0151] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0152] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is Al and the coating element is Ti. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0153] Embodiment 11 1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution, disperse the mixed solution by ultrasonication for 2 h, add ammonium phosphonate as a complexing agent, add it twice, the addition time is 2 h, the interval between the two times is 1 h, the first continuous addition time is 0.5 h, and the second continuous addition time is 0.5 h. The final concentration of ammonium phosphonate in the mixed solution is 0.5 mol / L, spray granulate the mixed solution, control the atomization flow rate to 12 L / min, the size of the atomized droplet D50 to 8 μm, and the pyrolysis temperature to 500 ° C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0154] (2) 500gNi precursor 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.0g Al2O3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 945°C for a primary sintering treatment to obtain a primary sintering product.
[0155] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 1100 g and the air pressure was controlled at 0.62 MPa. The specific surface area of the air flow milling product was 0.6 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.53.
[0156] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0157] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is Al and the coating element is Ti. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0158] Example 12 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonic treatment for 2 h. Add ammonium phosphonate as a complexing agent in two additions, the addition time is 3 h, the interval between the two additions is 2 h, the first addition time is 0.5 h, and the second addition time is 0.5 h. The final concentration of ammonium phosphonate in the mixed solution is 0.6 mol / L. Spray granulate the mixed solution, control the atomization flow rate to 8 L / min, the atomization droplet size D50 to 8 μm, and the pyrolysis temperature to 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0159] (2) 500gNi precursor 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.6g La2O3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0160] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 800 g and the air pressure was controlled at 0.52 MPa. The specific surface area of the air flow milling product was 0.54 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.46.
[0161] (4) 100 g of the air flow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 500°C. After screening, the positive electrode material was obtained.
[0162] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, in which the doping element is La and the coating element is Al. Since the amount of the doping and coating elements is difficult to determine accurately, it is not reflected in the chemical formula.
[0163] Embodiment 13 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add alcohol amine as a complexing agent in two additions. The addition time is 2 h. The interval between the two additions is 0.5 h. The first addition time is 0.5 h and the second addition time is 1 h. The final concentration of alcohol amine in the mixed solution is 0.6 mol / L. Spray granulate the mixed solution. The atomization flow rate is controlled to be 8 L / min. The size D50 of the atomized droplets is 8 μm. The pyrolysis temperature is 500 °C. The precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0164] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.4g WO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0165] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 1200 g and the air pressure was controlled at 0.65 MPa. The specific surface area of the air flow milling product was 0.55 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.4.
[0166] (4) 100 g of the air flow pulverized product was mixed with 0.4 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 500°C. After screening, the positive electrode material was obtained.
[0167] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, where the doping element is W and the coating element is Al. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0168] Embodiment 14 (1) Dissolve metal nickel, cobalt, and aluminum in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h, add alcohol amine as a complexing agent, and add it twice. The addition time is 2 h, the interval between the two times is 0.5 h, the first continuous addition time is 0.5 h, and the second continuous addition time is 1 h. The final concentration of alcohol amine in the mixed solution is 0.6 mol / L. The mixed solution is sprayed and granulated, and the atomization flow rate is controlled to be 8 L / min. The D50 size of the atomized droplets is 8 μm. The pyrolysis temperature is 500 ° C, and the precursor Ni is obtained. 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0169] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.4g WO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0170] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 600 g and the air pressure was controlled at 0.45 MPa. The specific surface area of the air flow milling product was 0.55 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.4.
[0171] (4) 100 g of the airflow pulverized product was mixed with 0.4 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 500°C. After screening, the positive electrode material was obtained.
[0172] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, where the doping element is W and the coating element is Ti. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0173] Embodiment 15 (1) Dissolve metal nickel, cobalt and manganese in nitric acid at a molar ratio of 55:15:30 to form a uniform mixed solution. Disperse the mixed solution by ultrasonication for 2.5 h. Add alcohol amine as a complexing agent in two additions. The addition time is 2 h. The interval between the two additions is 0.5 h. The first addition time is 0.5 h and the second addition time is 1 h. The final concentration of alcohol amine in the mixed solution is 0.6 mol / L. The mixed solution is sprayed and granulated. The atomization flow rate is controlled to be 8 L / min. The size of the atomized droplets is 8 μm. The pyrolysis temperature is 500 °C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0174] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 273.4g LiOH·H2O, and 1.4g WO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 940°C for a primary sintering treatment to obtain a primary sintering product.
[0175] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 1200 g and the air pressure was controlled at 0.45 MPa. The specific surface area of the air flow milling product was 0.55 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.65.
[0176] (4) 100 g of the air flow pulverized product was mixed with 0.4 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 500°C. After screening, the positive electrode material was obtained.
[0177] The chemical formula of the positive electrode material prepared in this embodiment is LiNi 0.55 Co 0.15 Mn 0.30 O2, where the doping element is W and the coating element is Al. Since the amounts of the doping and coating elements are difficult to determine accurately, they are not reflected in the chemical formula.
[0178] Comparative Example 1 (1) Dissolve metal nickel, cobalt and manganese in hydrochloric acid at a molar ratio of 55:15:30 to form a uniform mixed solution, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the atomization droplet size to 8 μm, and the pyrolysis temperature to 500 ° C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0179] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 220g Li2CO3 are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 970℃ for a primary sintering treatment to obtain a primary sintered product.
[0180] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 2000 g, the air pressure was controlled at 0.7 MPa, and the specific surface area of the air flow milling product was 1.5 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.4.
[0181] (4) 200 g of the air flow pulverized product was mixed with 0.3 g of ZrO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0182] The chemical formula of the positive electrode material prepared in this comparative example is LiNi 0.55 Co 0.15 Mn 0.30 O2, wherein the coating element is Zr. Since the amount of the coating element is difficult to determine accurately, it is not reflected in the chemical formula.
[0183] Comparative Example 2 (1) Dissolve metal nickel, cobalt and manganese in hydrochloric acid at a molar ratio of 55:15:30 to form a uniform mixed solution, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the atomization droplet size to 8 μm, and the pyrolysis temperature to 500 ° C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0184] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 245.2g LiOH·H2O are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 975°C for a primary sintering treatment to obtain a primary sintered product.
[0185] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 150 g, the air pressure was controlled at 0.2 MPa, and the specific surface area of the air flow milling product was 0.5 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.05.
[0186] (4) 200 g of the air flow pulverized product was mixed with 0.3 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 600°C. After screening, the positive electrode material was obtained.
[0187] The chemical formula of the positive electrode material prepared in this comparative example is LiNi 0.55 Co 0.15 Mn 0.30 O2, wherein the coating element is Ti. Since the amount of the coating element is difficult to determine accurately, it is not reflected in the chemical formula.
[0188] Comparative Example 3 (1) Dissolve metal nickel, cobalt and manganese sulfate in water at a molar ratio of 55:15:30 to form a uniform mixed solution, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the atomization droplet size to 12 μm, and the pyrolysis temperature to 500 ° C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0189] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 232g LiOH·H2O are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 970°C for a primary sintering treatment to obtain a primary sintering product.
[0190] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 2000 g and the air pressure was controlled at 0.5 MPa. The specific surface area of the air flow milling product was 0.9 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.6.
[0191] (4) 100 g of the airflow pulverized product was mixed with 0.2 g of TiO2, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 700°C. After screening, the positive electrode material was obtained.
[0192] The chemical formula of the positive electrode material prepared in this comparative example is LiNi 0.55 Co 0.15 Mn 0.30 O2, wherein the coating element is Ti. Since the amount of the coating element is difficult to determine accurately, it is not reflected in the chemical formula.
[0193] Comparative Example 4 (1) Dissolve metal nickel, cobalt and manganese in hydrochloric acid at a molar ratio of 55:15:30 to form a uniform mixed solution, spray granulate the mixed solution, control the atomization flow rate to 10 L / min, the atomization droplet size to 12 μm, and the pyrolysis temperature to 500 ° C to obtain the precursor Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2).
[0194] (2) 500g Ni 0.55 Co 0.15 Mn 0.30 O x (0.8<x<1.2), 93.8g LiOH·H2O are uniformly mixed, and the first mixture is placed in an oxygen atmosphere furnace at 960°C for a primary sintering treatment to obtain a primary sintering product.
[0195] (3) The primary sintered product was subjected to air flow milling. The grinding mass was controlled at 400 g, the air pressure was controlled at 0.7 MPa, and the specific surface area of the air flow milling product was 1.0 m 2 / g, and the average aspect ratio of the particles in the airflow milling product is 1.3.
[0196] (4) 100 g of the air flow pulverized product was mixed with 0.2 g of Al2O3, and a secondary sintering treatment was performed in an oxygen atmosphere furnace at 500°C. After screening, the positive electrode material was obtained.
[0197] The chemical formula of the positive electrode material prepared in this comparative example is LiNi 0.55 Co 0.15 Mn 0.30 O2, where the coating element is Al. Since the amount of the coating element is difficult to determine accurately, it is not reflected in the chemical formula.
[0198] Test Method (1) Particle distribution test of positive electrode materials: The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and the particle size in the SEM image is calculated using Nana Measure software. 200 particles in the SEM image are randomly measured, and the average size of the longest diameter of a single particle is D, the average size of the wide diameter that perpendicularly bisects the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L.
[0199] (2) Testing of metal elements in positive electrode materials: Take 0.3g of the sample to be tested and dissolve it in aqua regia, cool and dilute to a volume of 100ml to prepare the mother solution for determination; take 1mL of the mother solution for determination, dilute it 100 times, and test the content of the main elements Li, Ni, Co, and Mn and the content of other elements such as doping elements by ICP. The determination is carried out using Agilent 5110 ICP-OES detection equipment.
[0200] (3) Particle size test: The particle size distribution of the positive electrode material particles was obtained by using the laser diffraction light intensity distribution of the British Malvern Mastersizer 3000 model laser particle size analyzer. The volume-based cumulative particle size distribution of the particle size distribution determination was measured by the laser diffraction method, D 10 It indicates the particle size corresponding to the cumulative particle size distribution percentage of the powder reaching 10%, D 50 Indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 50%, D 90 It indicates the particle size corresponding to when the cumulative particle size distribution percentage reaches 90%.
[0201] Volume particle size distribution width of positive electrode material = (D 90 -D 10 ) / D 50 .
[0202] (4) Specific surface area test: The specific surface area of the material was calculated using the American TriStarⅡ surface area and pore analyzer by nitrogen adsorption and the BET method.
[0203] (5) Morphology test: The Hitachi S4800 scanning electron microscope was used to observe the surface morphology, particle size, etc. of the samples, and the SEM image of the positive electrode material was obtained.
[0204] (6) Tap density test of positive electrode material: Test of tap density ρ1: Dandong Better BT-303 was used to test the tap density, with a vibration rate of 3000 times / min, a vibration time of 1min, and a vibration amplitude of 3mm±0.1mm.
[0205] (7) Compaction density test of positive electrode materials: The compaction density ρ2 of the powder was tested using a compaction density meter with a pressure of 6t for 30s.
[0206] (8) XRD test analysis of positive electrode materials: The diffraction peak of the material is tested by XRD diffractometer, with a scanning speed of 1° / min, a step length of 0.005°, and a scanning range of 10-70° to obtain the diffraction peak of the material, and then the strain value of the ternary positive electrode material is calculated and output through XRD refinement of the diffraction peak. In the XRD refinement process, the calculation of microscopic strain and grain size is one of the key steps.
[0207] First, according to the Bragg equation and Scherrer formula, the calculation formula becomes: By analyzing and , which can be used to describe the degree of FWHM broadening caused by strain. In the Rietveld refinement process, the pseudo-Voigt function is used to represent the half-width (FWHM) of the diffraction peak function. Its formula is divided into two parts: Gaussian and Lorentzian, which contain parameters related to microscopic strain and grain size, respectively.
[0208] The specific formula is: Gaussian part: , the Lorentz part: , where U and Y are parameters related to microscopic strain, and X and P are parameters related to grain size, which correspond to the peak shape correction parameters GU, LY, LX and GP in the refinement process. Therefore, the lattice strain parameters can be obtained by deriving the four parameters after refining the peak shape of the measured XRD data and substituting them into the corresponding calculation formula.
[0209] The XRD diffractometer was used to test the XRD images in the range of 10°-70° at 1° / min and a step length of 0.005°. The XRD images were then refined by Rietveld using GASA software, with the refinement standard being RWP < 3%. After refinement, the unit cell volume, cell parameters c, a, cell parameter Dp, and cation mixing information can be obtained in the cell parameter interface of GSAS software, where Dp = D 003 +D 104 The average value of .
[0210] (9) The test method for the percentage of particles with cracks in the positive electrode material is as follows: Test on the proportion of particles with cracks in positive electrode materials: First, take the powder positive electrode material, mix the powder positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and make a pole piece. Use the pole piece as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with cracks to the total number of positive electrode material particles is counted, and the number of cracks is characterized by the ratio. The test results of this application are statistical results obtained by randomly selecting cross sections of about 300 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM images obtained from the test can represent the average level of the positive electrode materials tested. Since the pole pieces are not rolled during the production process in this test method, the crack number ratio obtained from the test can be regarded as the crack particle number ratio of the positive electrode material in the powder state.
[0211] Test on the proportion of positive electrode material particles with cracks in positive electrode sheets: First, take the powder positive electrode material, mix the positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, add NMP (N-methylpyrrolidone) to make a uniform slurry and apply it on aluminum foil, dry it in an oven, and roll it under a pressure of 10 Mpa to make a pole sheet. Use the pole sheet as a sample, and according to the standardized process of cross-section sample preparation, use an electron transmission microscope to focus the ion beam into a small-sized ion beam to bombard the surface of the sample to achieve sample peeling. The stripped sample is tested by scanning electron microscopy (SEM). Under a field of view of 3 k, the field of view of different areas is counted, and the proportion of the number of positive electrode material particles with cracks to the total number of positive electrode material particles is counted, and the number of cracks is characterized by the ratio. The test results of this application are the statistical results obtained by randomly selecting the cross-sections of 200 positive electrode material particles in the SEM image as samples. The SEM test requires random sampling of positive electrode materials and random selection of areas. The SEM image obtained from the test can represent the average level of the positive electrode material tested.
[0212] (10) Electrochemical performance evaluation using button half-cell: The positive electrode material was mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a mass ratio of 80:10:10, and NMP (N-methylpyrrolidone) was added to make a uniform slurry. The slurry was evenly coated on aluminum foil and placed in a 100°C oven for drying for 12 hours. After drying, it was rolled at a pressure of 10 MPa and cut into circular pole pieces with a diameter of 14 mm. The negative electrode used a Li metal sheet with a diameter of 14 mm. The lithium-ion battery was assembled according to the CR2025 button battery in industry. The diaphragm was Cellgard diaphragm, and the electrolyte used an equal amount of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. The positive pole piece, diaphragm, negative pole piece and electrolyte were assembled into a button battery in an Ar gas glove box with a water content and an oxygen content of less than 0.5 ppm.
[0213] Capacity test system: The blue electric test system is used for electrical performance testing (charge and discharge voltage is 3.0~4.4V, temperature condition is 25℃), 0.1C charging, 0.1C discharging, constant voltage cut-off current is 0.005C, and the discharge capacity mAh / g is calculated.
[0214] Cycle test system: At 25°C, charge and discharge voltage is 3.0~4.4V, charge and discharge cycle is 0.5C / 1C for 100 cycles, and the final capacity retention rate after 100 cycles is the cycle performance.
[0215] (11) Gas production value test of positive electrode materials: The positive electrode material, binder, conductive agent and carbon nanotubes were mixed in a mass ratio of 96:2:1.5:0.5 to make positive electrode sheets, and graphite, conductive agent and binder were mixed in a mass ratio of 95.4:1.2:3.4 to make negative electrode sheets. The separator was Cellgard separator, and the electrolyte was an equal mixture of ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) with 1 mol / L LiPF6 as the electrolyte. They were assembled into 2Ah soft-pack batteries, stored in a high-temperature oven at 60°C for 7 days, and the gas production was tested by the drainage method.
[0216] The above test results are detailed in Table 1~Table 2.
[0217] Table 1 Physical and chemical properties of cathode materials
[0218] Table 2 Electrochemical performance results of positive electrode materials
[0219] According to the test data of Examples 1 to 15, the present application controls the unit cell volume V of the positive electrode material while improving the unit cell parameter c / a ratio of the positive electrode material, so that c / a>4.82. As the c / a ratio increases, the layered structure has fewer defects, which is beneficial to the transmission of lithium ions and increases the rate, thereby compensating for the negative impact of the reduction in unit cell volume. By synergistically controlling the unit cell volume of the positive electrode material and the number of particles with cracks, the crystal structure stability of the positive electrode material can be effectively improved, particle breakage can be reduced, and the cycle stability of the positive electrode material can be improved. By regulating the unit cell parameter c / a of the positive electrode material, the rate performance of the positive electrode material can be improved, thereby achieving a comprehensive improvement in the cycle stability and gas production of the positive electrode material. Figure 2 and Figure 3 It can be seen that Figure 2 There are 5 particles with cracks in total. Figure 3 There are a total of 7 particles with cracks. The number of particles with cracks in the positive electrode material prepared in Comparative Example 1 accounts for a larger proportion than that in Example 1.
[0220] According to the test data of Examples 2 to 4, when the unit cell volume, unit cell parameters and the proportion of cracked particles of the positive electrode material are similar, the average length diameter of the particles in Example 4 is relatively large, that is, the roundness of a particle decreases. During the charge and discharge cycle of the particles, a small number of positive electrode material particles are prone to produce tiny cracks due to excessive local expansion pressure, and even cause particle rupture, which makes the cycle capacity retention rate of the positive electrode material slightly lower than that of Examples 2 and 3, and the gas production also increases.
[0221] According to the test data of Examples 5-6 and Examples 7-10, as the amount of the grinding body increases, the proportion of cracked particles in the positive electrode material also increases slightly, the cycle capacity retention rate of the positive electrode material decreases slightly, and the gas production also increases slightly. The number of particles with cracks in the positive electrode material of Example 13 accounts for the largest proportion, the side reaction between the positive electrode material and the electrolyte is intensified, and the gas production value also reaches the maximum.
[0222] According to the test data of Example 1 and Comparative Examples 1-2, since no flux was added during the primary sintering process, it was difficult to repair the cracks formed in the particles during the growth process, resulting in an increase in the proportion of particles with cracks in the positive electrode material, and the cycle capacity retention rate of the positive electrode material was significantly lower than that of Example 1, and the gas production value was also significantly increased.
[0223] According to the test data of Example 2 and Comparative Example 3, since no flux was added during the sintering process to increase the unit cell volume, and the degree of pulverization and dissociation was insufficient, the c / a ratio was too small, the number of defects in the crystal of the positive electrode material increased, and the capacity of the positive electrode material decreased compared with Example 2. In addition, the number of particles with cracks in the positive electrode material increased, the cycle capacity retention rate of the positive electrode material decreased significantly compared with Example 2, and the gas generation value also increased significantly.
[0224] According to the test data of Example 2 and Comparative Example 4, it can be seen that during the primary sintering process, no flux is added, which makes it difficult to repair the cracks formed in the particles during the growth process, resulting in an increase in the proportion of particles with cracks in the positive electrode material, and the cycle capacity retention rate of the positive electrode material is significantly lower than that of Example 2, and the gas production value is also significantly increased.
[0225] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is Li x Ni a Co b N c M d O2, 0.98≤x≤1.1, 0.5≤a<0.6, 0.08≤b≤0.14, 0.30≤c≤0.35, 0≤d≤0.10, a+b+c+d=1, N is Mn or Al, M is a metal element; A cross-sectional SEM image of the positive electrode material is measured at a magnification of 3K by a scanning electron microscope, and 200 particles in the cross-sectional SEM image are randomly measured, and the number of particles with cracks in the cross-sectional SEM image accounts for ≤13%; The positive electrode material is subjected to XRD measurement using Cu-Kα radiation, and the unit cell volume V of the positive electrode material is less than 104.2Å. 3 The relationship between the unit cell parameter c of the c-axis and the unit cell parameter a of the a-axis of the positive electrode material satisfies: c / a>4.
82.
2. The positive electrode material according to claim 1, characterized in that a≤2.901 Å, and / or, c≤14.2520 Å.
3. The positive electrode material according to claim 1, characterized in that The unit cell parameter Dp of the positive electrode material is 90 nm-120 nm, and / or the lattice strain of the positive electrode material is less than 0.3%.
4. The positive electrode material according to claim 1, characterized in that The M element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y.
5. The positive electrode material according to claim 1, characterized in that The volume particle size distribution width of the positive electrode material satisfies: 0.9≤(D 90 -D 10 ) / D 50 ≤1.
6.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The specific surface area of the positive electrode material is 0.5 m 2 / g~1.0m 2 / g; (2) The tap density of the positive electrode material is ρ1 g / cm 3 , 1.9<ρ1<2.7; (3) The compaction density of the positive electrode material is ρ2 g / cm 3 , 3.0≤ρ2<3.5; (4) The positive electrode material is a single crystal material, and the positive electrode material includes single crystal particles, and the particle size of the single crystal particles is 1 μm to 5 μm.
7. The positive electrode material according to claim 1, characterized in that The gas generation value of the positive electrode material is 0.1 mL / g to 1 mL / g.
8. The positive electrode material according to any one of claims 1 to 7, characterized in that The SEM image of the positive electrode material is measured by a scanning electron microscope at a magnification of 3K, and 200 particles in the SEM image are randomly measured. The average size of the longest diameter of a single particle is D, the average size of the wide diameter that perpendicularly bisects the longest diameter of the particle is L, and the average aspect ratio of the particles is α=D / L, 1≤α≤1.
6.
9. A positive electrode sheet, characterized in that: The positive electrode material comprises any one of claims 1 to 8, characterized in that, in the positive electrode sheet, the number of particles of the positive electrode material having cracks accounts for 1.5% to 13% of the total number of particles of the positive electrode material.
10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 8 or the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Nonaqueous Electrolyte Secondary Battery
CN106067559A
Lithium metal composite oxide powder, positive electrode active substance for lithium secondary battery, positive electrode, and lithium secondary battery
CN111837266A
Cathode active material, cathode containing same, and lithium secondary battery
WO2024210526A1
Cited By
Positive electrode material, preparation method thereof and sodium ion battery
CN120690856A
A positive electrode material, a preparation method thereof and a sodium ion battery
CN120690856B